Philosophical Theology in Islam : Later Ashʿarism East and West - Thiele, Jan,; Shihadeh, Ayman, (Islamicate Intellectual History;, 2020)
Philosophical Theology in Islam studies the later history of the Ashʿarī school of theology through in-depth probings of its thought, sources, scholarly networks and contexts. Starting with a review of al-Ghazālī's role in the emergence of post-Avicennan philosophical theology, the book offers a series of case studies on hitherto unstudied texts by the towering thinker Fakhr al-Dīn al-Rāzī as well as specific philosophical and theological topics treated in his works. Studies furthermore shed light on the transmission and reception of later Ashʿarī doctrines in periods and regions that have so far received little scholarly attention. This book is the first exploration of the later Ashʿarī tradition across the medieval and early-modern period through a trans-regional perspective. Contributors: Peter Adamson, Asad Q. Ahmed, Fedor Benevich, Xavier Casassas Canals, Jon Hoover, Bilal Ibrahim, Andreas Lammer, Reza Pourjavady, Harith Ramli, Ulrich Rudolph, Meryem Sebti, Delfina Serrano-Ruano, Ayman Shihadeh, Aaron Spevack, and Jan Thiele.